SISTEM INFORMASI PENILAIAN PEGAWAI NEGERI SIPIL DI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) TASIKMALAYA - Asep Saepulloh (JURNAL MANAJEMEN INFORMATIKA (JUMIKA), 2014)
The assessment work is a systematic way using a number of considerations, but certainly not eliminate the need to use a consideration. In practice in the field rather difficult to compile a list of assessment guidelines for the implementation of the right job. Because of this problem KPKNL Tasikmalaya tried using the standardized plan with the assessment of work based on the discipline and code of ethics.Given the importance of a valuation list in KPKNL Tasikmalaya implementation work, the authors conducted research in the form of observation, interview and literature study and summarized in the needs analysis and data analysis as a methodology of assessment of the implementation progress of this work list.To meet the information needs of the writer has about the system design and analysis of data processing employees, namely by studying the theories of supporters and collect data and information specifically related to the employee.With a system that has the author created it will achieve a rating list of guidelines implementation works correctly with the results of an output system of assessment information to employees.Keyword : Considerations, KPKNL, Implementation